PENGARUH IMPLEMENTASI MODEL PROJECT BASED LEARNING (PjBL) DENGAN BERBANTUAN FLIPPED CLASSROOM TERHADAP HASIL BELAJAR DAN MOTIVASI BELAJAR IPA SISWA KELAS VI - Syahyan Wibi Andriyani; Karta Sasmita; Mestika Sekarwinahyu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of the implementation of the Project Based Learning (PjBL) model assisted by Flipped Classroom on the learning outcomes and motivation to learn science of grade VI students at SD Negeri Karang Asih 06, North Cikarang District, Bekasi Regency. The study used a quasi-experimental method with a Treatment by Level (2x2) design in two groups, namely the experimental group using the PjBL model assisted by Flipped Classroom and the control group using conventional learning. Data collection was carried out through learning outcome tests and learning motivation questionnaires. The results showed that the average learning outcomes of students in the experimental group were higher (83.38) than the control group (73.00). The independent t-test showed a significant difference between the two groups (p <0.05), as well as the learning motivation of students in the experimental group experienced a significant increase. These findings prove that the implementation of the PjBL model assisted by Flipped Classroom is effective in improving learning outcomes and student motivation in science subjects.